Evaluation of prostate specific antigen in the prognosis of patients with advanced prostate cancer - Fonseca, Francisco Paulo da; Lopes, Ademar; Melarato Jr., Walter Antonio; Bachega Jr., Wilson; Marques, MarquesOsvaldo Junior Batista; Pereira, Raimunda Nonata (São Paulo Medical Journal, 1998)
OBJECTIVE: To evaluate the survival rate of patients with advanced prostate cancer in a univariate form, according to the preoperative and first postoperative determination of PSA levels. MATERIALS AND METHODS: From February 1987 to June 1995, 92 patients were submitted to maximum blockage androgen (subcapsular and antiandrogen orchiectomy), independent of clinical symptons shown upon admission to the Cancer Hospital. The antiandrogens (ciproterone acetate and flutamide) were administered until the patient present progression of the disease. RESULTS: The age of patients varied from 44 to 89, with a median of 70 years old. In the 6th, 36th and 60th months the global survival rate was 80%, 38% and 20%, respectively. The preoperative PSA ranged from 2 to 4017 ng/ml, with a median of 98 ng/ml (98% had PSA greater than or equal to 10 ng/ml). The first postoperative PSA ranged from 1 to 3840 ng/ml, with a median of 20 ng/ml. There was a tendency towards a better survival rate only in patients with initial PSA from 2 to 99 ng/ml (p=0.06745). The survival rate of patients at 36 months after the initial total blockage androgen, with first PSA level from 1 to 4, 5 to 49 and over 49 ng/ml was 72%, 48% and 8%, respectively (p=0.00004). In the final examination, 34 (37%) patients were considered stable and 58 (63%) had disease progression. CONCLUSION: The PSA determination performed on the 30th postoperative day is important in the evaluation of advanced prostate cancer prognosis.